Reaction of Different Rice Lines Against Leaf and Neck Blast under Field Condition Of Chitwan Valley - Puri, KD; Shrestha, SM; Joshi, KD; KC, GB (Journal of the Institute of Agriculture and Animal Science, 2006)
The severity of the rice blast disease (Pyricularia grisea) of both leaf and neck varies with different environment and it becomes destructive under favorable condition. The leaf and neck blast resistance and susceptible interaction of 30 different tropical rice lines were evaluated under low-, mid- and up-land conditions of Chitwan district and classified on the basis of disease severity with respect to susceptible check, Masuli. Of them, 5, 10, 12 and 3 rice lines were resistant to leaf blast, moderately resistant, moderately susceptible susceptible, respectively. Similarly, for the neck blast nine lines were resistant, thirteen moderately resistant, seven moderately susceptible and one was susceptible. The progenies from Masuli/MT4 had the highest leaf and neck blast susceptible reaction, while the most of progenies from IPB (Irradiated Pusa Basmati), KalinghaIII_IR64, Radha 32_ KIII and Masuli_IR64 were resistant, and the most promising sources against leaf and neck blast resistance. Therefore, the progenies from these parents can be used in breeding the resistant variety. Key words: Pyricularia grisea, resistance, rice lines J. Inst. Agric. Anim. Sci. 27:37-44 (2006)